Tight association of GRB2 with receptor protein-tyrosine phosphatase alpha is mediated by the SH2 and C-terminal SH3 domains. - den Hertog, J (1996)
Receptor protein-tyrosine phosphatase alpha (RPTPalpha), a transmembrane member of the extensive family of protein-tyrosine phosphatases (PTPs), is constitutively phosphorylated on Tyr789, a consensus binding site for the SH2 domain of the SH3-SH2-SH3 adaptor protein GRB2. We have previously shown that GRB2 binds to P.Tyr789 in vivo and in vitro via its SH2 domain. Here, we report that not only the GRB2 SH2 domain, but also the C-terminal SH3 domain is involved in binding to RPTPalpha in vitro and in vivo. Although the N-terminal SH3 domain of GRB2 is essential for binding to the Ras guanine nucleotide exchange factor Son of Sevenless (Sos), an RPTPalpha-GRB2-Sos complex could not be detected. The inclusion of peptides encompassing an hSos1 proline-rich motif in cell lysates resulted in enhanced binding of RPTPalpha to GRB2 in vitro, suggesting that steric hindrance prohibits formation of the RPTPalpha-GRB2-Sos complex. In vitro binding experiments indicated that the binding of GRB2 to Sos/dynamin and RPTPalpha was mutually exclusive. Analysis of in vitro binding kinetics coupled with results from transient co-transfections demonstrated that RPTPalpha is tightly bound to GRB2. The site of interaction of the C-terminal SH3 domain of GRB2 with RPTPalpha was mapped using deletion mutants to an 18-residue region in the N-terminal PTP domain. Arg469, within this region, was identified as one of the residues that is involved in the interaction with the C-terminal SH3 domain of GRB2. RPTPalpha residues 469-486 are localized close to the catalytic site cleft in the structure of the N-terminal PTP-domain, suggesting that interaction with the C-terminal SH3 domain may block access to the catalytic site, thus inhibiting RPTPalpha activity.